Kerja Sama Strategis Joint Venture dalam Bisnis Internasional dan Perlindungan Hukum Pihak Indonesia - Aryanti Agripina Winata; Gunardi Lie (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze the legal regulation of joint ventures in Indonesia as a form of Foreign Direct Investment (FDI) implemented through Limited Liability Companies based on Law Number 25 of 2007 concerning Investment, Law Number 40 of 2007 concerning Limited Liability Companies, and the Indonesian Civil Code. The research employs a normative legal method with a library research approach to examine legal provisions and concepts related to cooperation between foreign investors and domestic parties. The findings indicate the existence of structural imbalances between the parties, where foreign investors possess advantages in capital, technology, business experience, and access to information, resulting in asymmetrical bargaining power. This condition may lead to domination in decision-making, information gaps, and potential exploitation of domestic parties. Furthermore, existing legal protection is considered insufficient to fully implement the principle of equitable bargaining. Therefore, this study proposes a normative reconstruction through the application of principles of balance of power, good faith, transparency, and proportionality in joint venture agreements. The study also recommends preventive supervision through mandatory due diligence by the Financial Services Authority and the Investment Coordinating Board, including the standardization of contractual clauses and disclosure obligations, in order to create fair, sustainable joint venture relationships that protect national interests.